Application of social entrepreneurship in rubbish treatment innovative - Arniati Arniati; Muhammad Rusydi; Andi Arifwangsa Adiningrat; Muryani Arsal; Naidah Naidah; Warda Warda (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2025)
The urgency of social entrepreneurship application research refers to environmental problems such as increasing amounts of waste and environmental pollution. The purpose of this study is to examine the application of social entrepreneurship in innovative waste management at Arta Samudra. The research method used is a qualitative approach with data collection techniques through interviews. Practically, this study is an increase in the economy of Artha Samudra employee members, reduced waste volume and reduced environmental pollution. Theoretically, this study contributes to innovative social entrepreneurship in increasing business. The results of the study indicate that social entrepreneurship is effective in waste management through innovation. The novelty of this study emphasizes innovation in social entrepreneurship for waste management in rural areas. This study has implications in social, economic, and environmental aspects, and can be a reference for the development of more innovative and sustainable social entrepreneurship policies.